2014
DOI: 10.1021/jp411033h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structures and Absorption Spectra Assignment of Corrole NH Tautomers

Abstract: The individual absorption spectra of the two NH tautomers of 10-(4,6-dichloropyrimidin-5-yl)-5,15-dimesitylcorrole are assigned on the basis of the Gouterman four-orbital model and a quantum chemical TD-DFT study. The assignment indicates that the red-shifted T1 tautomer is the one with protonated pyrrole nitrogen atoms N(21), N(22) and N(23), whereas the blue-shifted T2 tautomer has pyrrole nitrogen atoms N(21), N(22) and N(24) protonated. A wave-like nonplanar distortion of the macrocycle in the ground state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
0
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 64 publications
8
73
0
5
Order By: Relevance
“…The lower energy region, from 500 to 650 nm, have absorption peaks that correspond to transitions from the corrole p system to the p* molecular orbitals of both the tetrapyrrolic ring and bipyridine, and, at 416 nm, there are transitions from the HOMO to the p* molecular orbitals of the bipyridine and fluorophenyl groups. Those are commonly assigned as the S 0 -S 1 and S 0 -S 2 transitions, respectively [37]. The orbital picture suggesting an electron jump from the HOMO of corrole 2 to the bipyrine is of particular importance, for it demonstrates the possibility of excited state electron transfer in a possible bimetallic complex involving the central ring and a peripheral metal.…”
Section: Theoretical Td-dft Resultsmentioning
confidence: 99%
“…The lower energy region, from 500 to 650 nm, have absorption peaks that correspond to transitions from the corrole p system to the p* molecular orbitals of both the tetrapyrrolic ring and bipyridine, and, at 416 nm, there are transitions from the HOMO to the p* molecular orbitals of the bipyridine and fluorophenyl groups. Those are commonly assigned as the S 0 -S 1 and S 0 -S 2 transitions, respectively [37]. The orbital picture suggesting an electron jump from the HOMO of corrole 2 to the bipyrine is of particular importance, for it demonstrates the possibility of excited state electron transfer in a possible bimetallic complex involving the central ring and a peripheral metal.…”
Section: Theoretical Td-dft Resultsmentioning
confidence: 99%
“…pyrrolenic ring) in meso-aryl-substituted corroles determines the distinct optical properties and reactivity toward protons for the corresponding NH-tautomers (T1 and T2, see Scheme 1 for the particular structures and assignments). [22][23][24][25][26] Moreover, evidences of the coexistence of two NH-tautomers in fluid solutions at room temperature have been presented. 22,26 In particular, it was found that two NH-tautomers differ in their basicity, which was supposed to be due to different out-of-plane (oop) distortions of the corrole macrocycle and, more specifically, due to out-of-plane tilting of the pyrrolenic ring to be protonated in the different NH-tautomers.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] Moreover, evidences of the coexistence of two NH-tautomers in fluid solutions at room temperature have been presented. 22,26 In particular, it was found that two NH-tautomers differ in their basicity, which was supposed to be due to different out-of-plane (oop) distortions of the corrole macrocycle and, more specifically, due to out-of-plane tilting of the pyrrolenic ring to be protonated in the different NH-tautomers. 22,26 In our recent work we focused on experimental assignment and quantum chemical calculations of the UV-vis absorption spectra, as well as on the static ground state geometries of the NH-tautomers of meso-pyrimidinylcorroles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations